SEX EDUCATION ACCORDING TO ISLAM FOR EARLY CHILDHOOD AND IMPLEMENTATION IN PAUD CURRICULUM - Azimah Nizar; Delfi Eliza (UPI Kampus Cibiru, 2021)
This research is based on the cases of abuse and violence against early childhood. The purpose of this study is to implement Islamic sex education for early childhood in the PAUD curriculum. The research method used is qualitative research; the subject was taken using purposive sampling. Research data was conducted using structured interviews with children, unstructured-planned interviews with the teacher, observation techniques with participant-observer form. The study results found that not all children had indicators of gender, body parts that should be covered, and body parts that should not be touched. The study's conclusion is the importance of implementing Islamic sex education for early childhood in the PAUD curriculum